Food choices and service evaluation under time constraints: the school lunch environment. Issue 12 (11th December 2017) - Sharma, Amit; Moon, Joonho; Bailey-Davis, Lisa; Conklin, Martha
Abstract : Purpose: Few states or local school districts mandate a minimum time for lunch. With increasing pressure on schools to maximize instructional time, many US students have witnessed continued reductions in the time allotted to lunch periods and, thus, less time to choose from an increasing number of food options. This study aims to investigate middle and high school students' preferences regarding the time available for school lunches and whether the amount of time would affect their food choice preferences. Design/methodology/approach: This study investigated students' self-reported lunchtime constraints and food choice preferences through a paper-and-pencil survey. The categorical and ratio responses were analyzed using ordinal logistic regression. Findings: Students responded that they rarely had enough time to eat school lunch and that the lunch line waiting time strongly or very strongly influenced their food choices. For the students for whom time available for lunch and time in the lunch line influenced what they ate, they were more likely to prefer limited food choices in several categories of the school lunch menu. Practical implications: Foodservice professionals who wish to actively promote better nutrition might consider practical ways to reduce the foodservice wait time for students. While making healthier default options (e.g. a fruit or fresh vegetable side) could increase service convenience, time required for students to make informed meal choices should not be compromised. Originality/value: Because lunch line waiting time is related to students' food choices, schools need to review the number and types of food choices offered in terms of whether they encourage students to make more healthful choices. This study offers a unique perspective on the relationship between time and individual food choices in the school lunch environment and how this relationship affects the quality of children's diets and their eating behaviors.